Mutation analysis and molecular modeling for the investigation of ligand-binding modes of GPR84 - Nikaido, Yoshiaki; Koyama, Yuuta; Yoshikawa, Yasushi; Furuya, Toshio; Takeda, Shigeki (Journal of biochemistry (Tokyo), 2015)
GPR84 is a G protein-coupled receptor for medium-chain fatty acids. Capric acid and 3,3'-diindolylmethane are specific agonists for GPR84. We built a homology model of a GPR84-capric acid complex to investigate the ligand-binding mode using the crystal structure of human active-state β2-adrenergic receptor. We performed site-directed mutagenesis to subject ligand-binding sites to our model using GPR84-Giα fusion proteins and a [(35)S]GTPγS-binding assay. We compared the activity of the wild type and mutated forms of GPR84 by [(35)S]GTPγS binding to capric acid and diindolylmethane. The mutations L100D `Ballesteros-Weinstein numbering: 3.32), F101Y (3.33) and N104Q (3.36) in the transmembrane helix III and N357D (7.39) in the transmembrane helix VII resulted in reduced capric acid activity but maintained the diindolylmethane responses. Y186F (5.46) and Y186H (5.46) mutations had no characteristic effect on capric acid but with diindolylmethane they significantly affected the G protein activation efficiency. The L100D (3.32) mutant responded to decylamine, a fatty amine, instead of a natural agonist, the fatty acid capric acid, suggesting that we have identified a mutated G protein-coupled receptor-artificial ligand pairing. Our molecular model provides an explanation for these results and interactions between GPR84 and capric acid. Further, from the results of a double stimulation assay, we concluded that diindolylmethane was a positive allosteric modulator for GPR84.